THE PERSONIFICATION OF FIGURATIVE WORDS IN TRUBUS MAGAZINE: A MODERN STYLISTICS STUDY - Imrotin, Imrotin; Badrih, Moh.; Famsah, Saefuddin; Busri, Hasan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Personification is one of the figurative languages used in casual and academic texts. One of the popular magazines that employs figurative language to attract readers is Trubus. The current study aims to analyze the classification, structure, rhyme words, lexical meaning, and imagery styles of personification in Trubus magazine. It is descriptive qualitative research using the Metaphor Identification Procedure (MIP) approach. The data source in this study is Trubus magazine, edition 2021. Data analysis covers the personification of figurative language's reduction, assessment, and inference. The result found that the personification style in this magazine belongs to inanimate objects, which tend to be abstract. Meanwhile, the rhyme words employ the beauty of the alliteration sound at the beginning of the word. Further, the grammatical structure is general. Lastly, grammatical, textual, and contextual fields contribute to meaning-making.